Pemanfaatan Limbah Serbuk Teh sebagai Substitusi Serbuk Gergaji terhadap Pertumbuhan Miselium dan Produksi Jamur Tiram Putih (Pleurotus Ostreatus) - Mardiana, Siti; Panggabean, Ellen L; Kuswardani, Retno A; Usman, Muhammad (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2018)
The waste of tea powder is abundant and has not been widely used optimally. The alternative use is to use the waste as an additional medium or substitution for the white oyster mushroom growing media. The purpose of the study was to determine the effect of mycelium growth and the production of the fruit of the white oyster mushroom on combination media / tea powder substitution with sawdust. The research design used was a completely randomized design (CRD) with 4 replications. Combined treatments were M0 = 100% sawdust; M1 = 100% Tea waste powder; M2 = 75% tea powder + 25% sawdust; M3 = 50% tea powder + 50% sawdust and M4 = 25% tea powder + 75% sawdust. All treatments used the composition of the manufacture of mushroom growing media consisting of each combination of treatments, bran 10% by weight of the material and lime 0.5% by weight of the material. The parameters observed were the growth of white oyster mushroom mycelium, the rate of mycelium growth, the time the mycelium closed the substrate, the time of appearance of the fruiting body, the weight of the fruit body and the diameter of the fruit hood. The results showed that all parameters differed significantly. The best treatment is in treatment M4, followed by treatment of M3, M0 and M2.